2011
DOI: 10.1089/jwh.2010.2371
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Among Depression, Anxiety, and Insomnia Symptoms in Perinatal Women Seeking Mental Health Treatment

Abstract: Insomnia symptoms affected a significant proportion of the perinatal women in this sample. These symptoms are linked to symptoms of depression and anxiety in treatment-seeking pregnant and postpartum women. Perinatal women seen in psychiatric treatment settings should be routinely screened for sleep problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
76
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(87 citation statements)
references
References 24 publications
10
76
1
Order By: Relevance
“…The observed rate of clinically significant insomnia in the presence of a high level of depressive symptom severity (46.7%) is comparable to that reported by Swanson et al, 59 who found that 45% of pregnant women in a universityaffiliated outpatient psychiatry clinic had clinically significant insomnia, which the researchers defined as ISI scores above 14. At the same time, the observed rate of clinically significant insomnia among pregnant women with low depression scores (8%) in our study was similar to rates observed in the general population.…”
Section: Discussionsupporting
confidence: 82%
“…The observed rate of clinically significant insomnia in the presence of a high level of depressive symptom severity (46.7%) is comparable to that reported by Swanson et al, 59 who found that 45% of pregnant women in a universityaffiliated outpatient psychiatry clinic had clinically significant insomnia, which the researchers defined as ISI scores above 14. At the same time, the observed rate of clinically significant insomnia among pregnant women with low depression scores (8%) in our study was similar to rates observed in the general population.…”
Section: Discussionsupporting
confidence: 82%
“…A strength of this study is that it replicates key findings from recent work focusing on depressive and anxiety symptoms among non-clinical samples (Bei et al, 2010;Skouteris et al, 2009;Swanson et al, 2011;Wu et al, 2014). Instead of excluding women with high symptoms (Wu et al, 2014), we used borderline cut-offs, as mild depressive and anxiety symptoms are more common in the general population.…”
Section: Discussionsupporting
confidence: 73%
“…Indeed, more recent studies found that subjective sleep quality during pregnancy was associated with (Skouteris et al, 2009) or had additive effects on postnatal depression (Bei et al, 2010;Wu et al, 2014). Although a few previous studies found that poor subjective prenatal sleep quality was also correlated with higher levels of postnatal anxiety (Skouteris et al, 2009;Swanson et al, 2011), a recent review found not enough evidence (Lawson et al, 2015).…”
Section: Introductionmentioning
confidence: 98%
“…41 Several studies of pregnant women report high rates of insomnia symptoms. Swanson et al 42 reported that 45% of pregnant women scored above the threshold value, and Fernandez-Alonso et al 43 identified more than 73% in late pregnancy. Manber and colleagues, 44 however, reported that only 17% of Latina women, across all trimesters, met criteria for insomnia (≥ 10) and that there was no difference across trimesters.…”
Section: S C I E N T I F I C I N V E S T I G At I O N Smentioning
confidence: 99%